Danger Goes Berserk - Barnett, Mac; Myers, Matthew (New York : Simon & Schuster Books for Young Readers, 2012)
As soon as twelve-year-old Steve Brixton opens a detective office in his backyard, he and his best friend Dana are caught up in a tangle of cases, from breaking up a ring of piratical smugglers, to recovering a stolen surfboard, to tracking down a fifth-grader's missing gym shorts.
Keywords: Smuggling -- Fiction; Theft -- Fiction; Lost and found possessions -- Fiction; Books and reading -- Fiction; Mystery fiction; Humorous fiction